2023
DOI: 10.1029/2023sw003443
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient, Time‐Dependent High Speed Stream Model and Application to Solar Wind Forecasts

Abstract: A continuous stream of plasma blows out from the solar atmosphere, spreading out into interplanetary space. This so-called solar wind is not uniform, but rather contains distinct regions of fast (≳600 km/s) and slow (300-400 km/s) plasma flows. The fast solar wind is known to originate along the open magnetic field lines emanating from coronal holes (CHs; e.g., Cranmer, 2009) but there is less consensus on the source of the slow wind (see Cranmer et al., 2017, for a review on the origins of the ambient solar w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…MEOW-HISS uses three regions to represent the SIR, one for the HSS plateau, and another for the tail, in addition to the upstream and downstream regions (ahead of and behind the HSS, respectively). Kay et al (2023) first found the location of the region boundaries within each profile. For each CH, a regression was performed to get each boundary location as a function of time.…”
Section: Meow-hissmentioning
confidence: 99%
See 4 more Smart Citations
“…MEOW-HISS uses three regions to represent the SIR, one for the HSS plateau, and another for the tail, in addition to the upstream and downstream regions (ahead of and behind the HSS, respectively). Kay et al (2023) first found the location of the region boundaries within each profile. For each CH, a regression was performed to get each boundary location as a function of time.…”
Section: Meow-hissmentioning
confidence: 99%
“…In operation, MEOW-HiSS runs in reverse of the development with the CH area determining the distance coefficients, then the distance coefficients determining the critical values, which then establish the segment within a region. Kay et al (2023) contains a more detailed description of the development and use of MEOW-HiSS.…”
Section: Meow-hissmentioning
confidence: 99%
See 3 more Smart Citations